Legal Protection for Retail Investors in the Use of Financial Technology (FINTECH) - Lista Ade Sumiati Bondar; Martono Anggusti; Sovia Febrina Tamaulina Simamora (PT FORMOSA CENDEKIA GLOBAL, 2025)
The rapid development of financial technology (fintech) has brought convenience in various aspects of financial transactions, including for retail investors. Despite providing new opportunities, fintech also presents challenges related to legal protection for retail investors, given the lack of clear regulations and the potential risks of fraud, platform bankruptcy, and financial loss. This study aims to examine the existing legal protection for retail investors in the use of fintech in Indonesia. Using an analytical descriptive approach, this study analyzes the existing regulations, as well as the protection mechanisms provided by the Financial Services Authority (OJK) and Bank Indonesia (BI). The results show that although regulations are in place, there are some gaps that need to be addressed, especially in terms of fintech platform transparency and investor rights. This research suggests the need for strengthened regulation and increased supervision to create a safer and fairer fintech ecosystem for retail investors. One of the main challenges is the difficulty in implementing regulations that are flexible but still provide adequate protection for retail investors, given the many fintech business models that continue to emerge.